High-Frequency Notable HBV Mutations Identified in Blood Donors With Occult Hepatitis B Infection From Heyuan City of Southern China - Ye, Xianlin; Liu, Lihua; Chen, Lina; Nie, Xianghui; Huang, Lu; Ye, Denghuang; Zeng, Jinfeng; Li, Tong; Li, Bin; Xu, Min; Chen, Limin (Frontiers in Immunology, 2022)
Background All Chinese blood centers have implemented mini pool (MP) HBV nucleic acid testing (NAT) together with HBsAg ELISA in routine donor screening since 2015. The prevalence of occult hepatitis B virus infection (OBI) in donors from different regions varies, and the molecular characterization of the HBV DNA and clinical outcomes of these OBIs remain largely unexplored. Methods Blood donations from Heyuan city in Southern China were screened by HBsAg ELISA and HBV MP8 NAT. Donations with HBsAg-/HBV DNA+ were collected for this study. Molecular characterizations of HBV DNAs were further analyzed by various DNA amplification assays including quantitative PCR (qPCR) and nested PCR, amplifying the basic core and pre-core promoter regions (BCP/PC). The HBsAg (S) region from HBV DNA was isolated by high-volume nucleic acid extraction. Notable mutations were identified by comparison to the HBV reference sequences. The clinical outcomes of the donors with OBIs were further followed for nearly 3 years. Results Seventy OBIs from 44,592 donations (0.15%) that we identified and reported previously were enrolled for this current study. HBV sequences were obtained from 44/70 OBIs, and genotyping analysis showed that 42/44 (95.2%) OBIs were genotype B, and 2/44 (4.8%) were genotype C. Interestingly, mutation analysis revealed that various mutations including M133L/T, F134L, P142L, V168A, R169H, S174N, L175S, and V177A of HBV DNA affecting HBsAg detection were observed in genotype B OBIs. Two notable mutations, T47K and L53S, were identified in genotype C OBIs. Follow-up studies showed that 3/31 (9.7%) OBIs converted to HBsAg+ as chronic infections while 1/31 (3.2%) HBV DNA was undetectable (classified as recovery) and 27/31 (87.1%) remained as OBIs. Conclusion Various notable mutations affecting HBsAg detection were observed in blood donors with OBIs in Heyuan city of Southern China. Follow-up studies showed that most OBIs remained as OBIs with fluctuating or low viral loads. Higher sensitive HBV ID NAT is recommended for donor screening to further reduce the transmission risk of OBIs.